Integrated stratigraphy of the Bartonian-Priabonian Urtsadzor section, Armenia - Cotton, L. J.; Zakrevskaya, E. Y.; Boon, A. van der; Asatryan, G.; Hayrapetyan, F.; Israyelyan, A.; Krijgsman, W.; Less, G.; Monechi, S.; Musatov, V.; Pearson, P. N.; Razumovskiy, A.; et al. (2015)
The uppermost Bartonian to lowermost Priabonian transition is associated with several rapid extinctions across microfossil groups. However, the marker for the Bartonian-Priabonian boundary is not formally defined and currently under discussion. The planktonic foraminifera Acarinina and Morozovelloides suffer a rapid global extinction and calcareous nannofossils show several assemblage changes including the last occurrences of Sphenolithus obtusus and Chiasmolithus grandis, the acme of Cribrocentrum erbae and first occurrences of Chiasmolithus oamaruensis, Isthmolithus recurvus and Cribrocentrum isabellae around this interval. Within the shallow water, larger foraminifera also show an extinction of the large species of the genus Nummulites, as well as the first occurrences of important genera, such as Spiroclypeus and Pellatispira the upper middle Eocene. However, the exact correlation between shallow and deep water records remains uncertain, as do the mechanisms driving these extinction events. Here we present the first results of a new integrated stratigraphical study (calcareous nannofossils, planktonic foraminifera, larger benthic foraminifera, and magnetostratigraphy) of the Urtsadzor section in south-western Armenia which appears to be continuous through this interval. The Urtsadzor section consists of marlstones rich in micro- and nannofossils, with interbedded limestones containing abundant larger foraminifera. Our new data enable us to correlate larger foraminiferal events with global planktonic biostratigraphy, in a section outside of southwest Europe where most previous correlations have been based. At Urtsadzor, the large Nummulites species N. millecaput, appear to decrease in abundance toward the top of the section. The first occurrence of Spiroclypeus occurs in the uppermost limestone bed. These larger foraminiferal events occur well above the planktonic foraminiferal extinction level and nannofossil assemblage changes indicating the event is not synchronous across all groups, and has important ...